Analisis Makna dan Pelesetan Berbahasa pada Stiker Media Percakapan Whatsapp Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Riau - Nova Ardila Ningsih; Ayu Wandira; Irdiana Suhailanisa; Sindi Lesmana (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The way to communicate that is widely used by young people today is through the electronic media whatsapp, where this application can send text, images, stickers, and so on. A sticker consisting of supporting text and images can be used as an expression of the feelings that are being felt by the sender of the sticker. This study uses qualitative research, the method used is the library method which was carried out in 2022. The object used in this study is a sticker on social media obtained from social media or Whatsapp communication media. In collecting data, the researcher used a purposive technique, namely by collecting several stickers in the form of text and images, in Indonesian and the regional language, namely Javanese as a supporter of the stickers. The researcher found 10 data in the form of stickers from Whatsapp Groups, 6 data discussing the relationship between text and images on stickers and 4 data discussing semantic puns on stickers equipped with supporting images. The data obtained are categorized into two forms. This digital sticker serves as a communication material and a humor function.